Potential coolants for fuel cell application: Multi-objective optimization of thermophysical properties and PPF calculation of hybrid palm oil nanofluids - Nurhanis Sofiah, Abd Ghafar; Pasupuleti, Jagadeesh; Samykano, Mahendran; Rajamony, Reji Kumar; Pandey, Adarsh Kumar; Nur Fatin, Sulaiman; Zatil Amali, Che Ramli; Tiong, Sieh Kiong; Koh, Siaw Paw (Elsevier Ltd, 2024)
In this study, Response Surface Methodology (RSM) is being used to optimize density, viscosity, and thermal conductivity in CuO-polyaniline/palm oil hybrid nanofluids. Using a Central Composite Design (CCD) within RSM, researchers are systematically exploring the impact of temperature (ranging from 30 to 60 °C), volume concentration of nanoadditives (varying from 0.1 to 0.5 vol%) and CuO composition (ranging from 1 to 10 wt%) on the thermophysical properties of these nanofluids. This research is pioneering in its evaluation of the price performance factor (PPF) for these nanofluids. To ensure model reliability, Analysis of Variance (ANOVA) is being applied. The findings showcase robust models, as indicated by a 45° angle line within the predicted vs. actual data graph. The models exhibit impressive R2 values: 98.66 % for density, 99.93 % for viscosity, and 99.91 % for thermal conductivity, underscoring the agreement between predicted and actual data. Optimal values for density, viscosity, and thermal conductivity are being obtained: 0.901532 g/mL, 37.1229 mPa s, and 0.356891 W/mK, respectively. These correspond to critical parameters of 53.92 °C for temperature, 0.038 vol% for volume concentration of nanoadditives and 2.90 wt% for CuO composition. Moreover, the price performance factor (PPF) assessment reveals that higher thermal conductivity doesn't necessarily equate to greater cost-effectiveness.